EBI Metagenomics in 2017: enriching the analysis of microbial communities, from sequence reads to assemblies. Issue Volume 46:Issue D1(2018) (23rd October 2017) - Mitchell, Alex L; Scheremetjew, Maxim; Denise, Hubert; Potter, Simon; Tarkowska, Aleksandra; Qureshi, Matloob; Salazar, Gustavo A; Pesseat, Sebastien; Boland, Miguel A; Hunter, Fiona M I; ten Hoopen, Petra; Alako, Blaise; et al.
Abstract: EBI metagenomics (http://www.ebi.ac.uk/metagenomics ) provides a free to use platform for the analysis and archiving of sequence data derived from the microbial populations found in a particular environment. Over the past two years, EBI metagenomics has increased the number of datasets analysed 10-fold. In addition to increased throughput, the underlying analysis pipeline has been overhauled to include both new or updated tools and reference databases. Of particular note is a new workflow for taxonomic assignments that has been extended to include assignments based on both the large and small subunit RNA marker genes and to encompass all cellular micro-organisms. We also describe the addition of metagenomic assembly as a new analysis service. Our pilot studies have produced over 2400 assemblies from datasets in the public domain. From these assemblies, we have produced a searchable, non-redundant protein database of over 50 million sequences. To provide improved access to the data stored within the resource, we have developed a programmatic interface that provides access to the analysis results and associated sample metadata. Finally, we have integrated the results of a series of statistical analyses that provide estimations of diversity and sample comparisons.